Implementasi Strategi Manajemen Ritel Pada PT. Bumi Nyiur Swalayan - Kori Nurfadilah; Ponirin Ponirin; Harnida Wahyuni Adda (Pusat Riset dan Inovasi Nasional, 2023)
Today the development of the retail business in Indonesia shows a very positive trend. This is shown by the ever-increasing number of minimarkets in Indonesia. This research was conducted at PT. Bumi Nyiur Swalayan and aims to determine the implementation of retail management strategies at PT. Bumi Nyiur Supermarket head office. This research is a qualitative research and primary data sources using data collection techniques, namely observation and interviews. The results of the study show that the implementation uses four management aspects, namely marketing aspects, production aspects, human resource management aspects and financial aspects.